The Social Impact of Musical Engagement for Young Adults With Learning Difficulties: A Qualitative Study - Wilson, Graeme B.; MacDonald, Raymond A. R. (Frontiers in Psychology, 2019)
There is evidence that music interventions can offer opportunities for creative, psychological and social developments for individuals with mild to profound learning disabilities, addressing the disadvantages they face in respect of social outcomes. This paper reports on a qualitative study investigating a community music intervention for such a population. Thirty-seven adult service users (12 female, 25 male) took part in weekly music workshops for ten weeks. Their learning difficulties ranged from mild to profound, and their levels of independence ranged from requiring constant one-to-one care to living alone in sheltered accommodation. Interviews were conducted at multiple time points with music and resource centre staff as well as participants and members of their families and other centre users; researchers also observed all workshops, taking field notes. Thematic analysis of the data informed understanding of the disadvantages facing participants, their experience of the workshop programme and its immediate and wider social outcomes, as well as suggesting key mechanisms for effects. Disadvantages and barriers facing participants included: limited access to enjoying or learning music; boredom, isolation and limited networks; lack of experience of new social contexts; and an associated lack of confidence, low mood or self-esteem. Participants were found to enjoy and sustain engagement with a programme of dedicated group music workshops delivered by staff trained in an empathic and inclusive approach. Impacts included an ongoing enthusiasm to engage in music; wider recognition of musicality; increased self-confidence; being happier, more relaxed and/or enthusiastic after the workshops; better ability to interact with unfamiliar situations and people; and participation in social activities for an unprecedented length of time. Key factors in achieving those impacts are that participants: had fun and interacted socially; felt secure, welcomed and involved at all times; exercised choice; worked with others in non-verbal tasks; and encountered challenge while engaging and progressing at their own rate.